Analysis of Internalization Project To Strengthen The Profile Of Pancasila Students Based on Local Culture Of Toraja - Kaban Sendana, Aris; Nani Sallata, Yizrel; Teko Patanduk, Sushy (Universitas Cokroaminoto Palopo, 2025)
This study explores the internalization of the